INFLUÊNCIA DE ADIÇÕES MINERAIS POZOLÂNICAS E DE FINOS DE PEDREIRA NAS PROPRIEDADES MECÂNICAS E NA MICROESTRUTURA DO CONCRETO AUTO-ADENSÁVEL - ARAÚJO, Janaína das Graças (2007)
For the benefits of its properties in fresh state, self-compacting concrete (SCC) demands a high powder content in the composition, nearby 450kg/m³. The quarry dust, resultant material of the coarse aggregate production, can b considered as an economic and sustainable alternative for the development of the SCC. As well as the quarry dust, mineral additions, is used in conventional concretes and can also be used in the self-compacting concrete, with the same kind of benefits. Using the mix design for SCC developed by Tutikian (2004) a study for evaluation of the SCC mechanical properties were done, where natural sand had been partially replaced by quarry micaschist, granite and gneiss - and cement for silica fume, metakaolin and calcined clay pozolan. The test methods for fresh state used was Slump-flow (FURNAS, 2005a), U-Box (FURNAS, 2005b), Entrained air (NM 47, 2002) and Specific gravity (9833, 1997). Cylindrical test specimen 100x200 mm had been molded for tests - compressive strength (NBR 5739, 1994), modulus of elasticity (NBR 8522, 1984), splitting tensile strength (NBR 7222, 1994) and flexural strength (NBR 12142, 1991) -the age of 28 days. Samples using the mixture1: 4,5 had been analyzed by scanning electron microscope (SEM). The results show that it can be possible the use of different additions for the production of high quality SCC. We detach the small variability of the specific gravity, as well as the entrained air, wide presented low values. For concretes with same compressive strength, the values of modulus of elasticity had varied between 5 and 60% and the splitting tensile strength and flexural strength had been remained between 10 and 15%